Penerapan Model Pembelajaran Discovery Learning Berbantuan Media Gambar Untuk Meningkatkan Hasil Belajar IPA Pada Siswa Kelas IV SD Inpres Koperapoka II - Norvi Seno Linggi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research began with problems in science learning in class IV of SD Inpres Koperapoka II where the majority of students had difficulty understanding science learning material, so that the learning outcomes obtained by students were low. Therefore, to improve student learning outcomes in science learning, a discovery learning model assisted by image media is used for fourth grade students at SD Inpres Koperapoka. This research is classroom action research (PTK) using a qualitative approach. This research was carried out on fourth grade students at SD Inpres Koperapoka II with a total of 24 students. The instruments used to collect data are observation sheets, documentation and learning outcomes tests. The data obtained in the research was analyzed using qualitative and quantitative data analysis. This research was carried out in two cycles and each cycle consisted of one meeting. The results of research from each cycle that has been carried out using the discovery learning learning model assisted by image media show an increase in both the learning process and student learning outcomes. This can be seen from students' achievements in learning, where in cycle I the average score obtained by students only reached 70.8% completeness with an average student score of 68.75, while in cycle II showed quite a high increase with completeness reaching 87.5% and the average student score is 82. Thus it can be concluded that the use of the discovery learning learning model assisted by image media can improve student learning outcomes in science learning in class IV of SD Koperapoka II.